Modelled climatic suitability contraction and high-altitude persistence: Projected mid-century distribution dynamics of Ophiocordyceps sinensis across the Tibetan Plateau under a selected climate scenario - Qiuyang Wei; Yuanchuan He; Shijiang Chen (PLoS ONE, 2026)
Ophiocordyceps sinensis , a vulnerable fungal resource endemic to the Tibetan Plateau, faces climatically driven habitat degradation under ongoing climate change. Existing studies document its distribution but rarely address temporal dynamics under ongoing climate shifts. To fill this research gap, we implemented five-fold spatial block cross-validation (SBCV)-enhanced MaxEnt modelling and quantified extrapolation risks via Multivariate Environmental Similarity Surfaces (MESS; mean = 0.734 ± 0.135) using 201 spatially filtered occurrence points. Model performance was primarily evaluated via geographically independent spatial validation, yielding a mean test area under the receiver operating characteristic curve of 0.953 ± 0.002, confirming robust spatial transferability across the Tibetan Plateau. Integration of static topographic and dynamic bioclimatic variables across past–current–future timelines enabled validation against historical baselines (1970–2000), followed by Shared Socioeconomic Pathways 3–7.0 (SSP3–7.0) scenario projections. Elevation and warmest-quarter precipitation emerged as dominant predictors, collectively explaining 91.3% of habitat suitability. Under the BCC-CSM2-MR model and SSP3–7.0 scenario, conditional projections indicate severe near-term climatic suitability contraction (54% loss in modelled suitable habitat area relative to the 1970–2000 historical baseline, from 396,000 km 2 to 182,000 km 2 by 2021–2040), with over 82% of this total loss concentrated in marginal zones. Driven by localized expansion in the Tanggula Mountains that offsets low-elevation declines, the total modelled suitable habitat area stabilized at 198,000 km 2 , accounting for 3.78% of China’s land area, during the mid-century (2041–2060) under this model-scenario combination. This validated framework provides conditional insights for identifying potential climate refugia of O. sinensis and supporting evidence-based climatic suitability assessments.